A note on digital elevation model smoothing and driving stresses - McCormack, Felicity S; Roberts, Jason L; Jong, Lenneke M; Young, Duncan A; Beem, Lucas H (Polar Research, 2019)
Ice-flow fields, including the driving stress, provide important information on the current state and evolution of Antarctic and Greenland ice-sheet dynamics. However, computation of flow fields from continent-scale DEMs requires the use of smoothing functions and scales, the choice of which can be ad hoc. This study evaluates smoothing functions and scales for robust calculations of driving stress from Antarctic DEMs. Our approach compares a variety of filters and scales for their capacity to minimize the residual between predicted and observed flow direction fields. We find that a spatially varying triangular filter with a width of 8–10 ice thicknesses provides the closest match between the observed and predicted flow direction fields. We use the predicted flow direction fields to highlight artefacts in observed Antarctic velocities, demonstrating that comparison of multiple observational data sets has utility for quality control of continent-scale data sets.
Keywords: Antarktis; geofysikk; glasiologi; innlandsis; isbreer; istykkelse

Groundwater discharge to the western Antarctic coastal ocean - Null, Kimberly A; Corbett, D Reide; Crenshaw, Jared; Peterson, Richard N; Peterson, Leigha E; Lyons, W Berry (Polar Research, 2019)
Submarine groundwater discharge (SGD) measurements have been limited along the Antarctic coast, although groundwater discharge is becoming recognized as an important process in the Antarctic. Quantifying this meltwater pathway is important for hydrologic budgets, ice mass balances and solute delivery to the coastal ocean. Here, we estimate the combined discharge of subglacial and submarine groundwater to the Antarctic coastal ocean. SGD, including subglacial and submarine groundwater, is quantified along the WAP at the Marr Glacier terminus using the activities of naturally occurring radium isotopes (223Ra, 224Ra). Estimated SGD fluxes from a 224Ra mass balance ranged from (0.41 ± 0.14)×104 and (8.2 ± 2.3)×104m3 d−1. Using a salinity mass balance, we estimate SGD contributes up to 32% of the total freshwater to the coastal environment near Palmer Station. This study suggests that a large portion of the melting glacier may be infiltrating into the bedrock and being discharged to coastal waters along the WAP. Meltwater infiltrating as groundwater at glacier termini is an important solute delivery mechanism to the nearshore environment that can influence biological productivity. More importantly, quantifying this meltwater pathway may be worthy of attention when predicting future impacts of climate change on retreat of tidewater glaciers.
Keywords: Sørishavet; biologi; geologi; grunnvann; hydrologi; isbreer; klimaendringer; tidevann

Mapping glacier-related research in polar regions: a bibliometric analysis of research output from 1987 to 2016 - Liang, Qi; Peng, Sha; Niu, Beibei; Zhou, Chunxia; Wang, Zhen (Polar Research, 2018)
We carried out a bibliometric analysis of literature related to glaciers in polar regions from the period 1987–2016 indexed in the Science Citation Index Expanded database. A comprehensive review was performed by analysing the research output trends, publication categories, main journals, leading countries and their collaborations, leading scientists, author keywords and Keywords Plus. The results indicated that the number of publications related to glaciers in polar regions has increased rapidly. The USA and several European countries, including the UK, France, Germany and Switzerland, are the leaders in the field of glacial studies, as reflected both in the productivity measures and in the distribution of core scientists. Quaternary Science Reviews, the Journal of Glaciology, and Geophysical Research Letters were the most productive journals for glacial studies. The synthesized analysis of the keywords demonstrated the current research emphases and hinted at future research trends. Reconstructing past climate changes through studies of ice-core records is one of the most important research subjects. Numerical modelling has become a commonly used tool in polar region glacial research. A better understanding of the responses of glaciers to widespread climatic warming is needed now and in the future.
Keywords: Antarktis; bibliometri; glasiologi; isbreer; klimaendringer; litteratur; miljøendringer; polarområdene

Local controls on sediment accumulation and distribution in a fjord in the West Antarctic Peninsula: implications for palaeoenvironmental interpretations - Munoz, Yuribia P.; Wellner, Julia S. (Polar Research, 2016)
We analyse surface sediment and its distribution in Flandres Bay, West Antarctic Peninsula, in order to understand modern day sediment dispersal patterns in a fjord with retreating, tidewater glaciers. The surface sediment descriptions of 41 cores are included in this study. The sediment facies described include muddy diatomaceous ooze, diatomaceous mud, pebbly mud, sandy mud and mud, with scattered pebbles present in most samples. In contrast to a traditional conceptual model of glacial sediment distribution in fjords, grain size in Flandres Bay generally coarsens from the inner to outer bay. The smallest grain size sediments were found in the bay head and are interpreted as fine-grained deposits resulting from meltwater plumes and sediment gravity flows occurring close to the glacier front. The middle of the bay is characterized by a high silt percentage, which correlates to diatom-rich sediments. Sediments in the outer bay have a high component of coarse material, which is interpreted as being the result of winnowing from currents moving from the Bellingshausen Sea into the Gerlache Strait. Palaeoenvironmental reconstructions of glacial environments often use grain size as an indicator of proximity to the ice margin. After a detailed analysis of a large number of cores collected in the study area, our findings highlight the variability in sedimentation patterns within a fjord and provide a valuable evidence of the complexity that may occur in the sedimentary record. Keywords: Flandres Bay; Antarctic Peninsula; sediment distribution; grain size.
Keywords: Antarktis; havbunnen; isbreer; miljøvitenskap; sedimenter; sedimentologi; topografi

Evolution of Derwael Ice Rise in Dronning Maud Land, Antarctica, over the last millennia - Drews, Reinhard; Matsuoka, Kenichi; Martín, Carlos; Callens, D; Bergeot, Nicolas; Pattyn, Frank (Journal of Geophysical Research: Earth Surface, 2015)
Ice rises situated in the ice-shelf belt around Antarctica have a spatially confined flow regime with local ice divides. Beneath the divides, ice stratigraphy often develops arches with amplitudes that record the divide's horizontal residence time and surface elevation changes. To investigate the evolution of Derwael Ice Rise, Dronning Maud Land, Antarctica, we combine radar and GPS data from three consecutive surveys, with a two-dimensional, full Stokes, thermomechanically coupled, transient ice-flow model. We find that the surface mass balance (SMB) is higher on the upwind and lower on the downwind slopes. Near the crest, the SMB is anomalously low and causes arches to form in the shallow stratigraphy, observable by radar. In deeper ice, arches are consequently imprinted by both SMB and ice rheology (Raymond effect). The data show how arch amplitudes decrease as along-ridge slope increases, emphasizing that the lateral positioning of radar cross sections is important for the arch interpretation. Using the model with three rheologies (isotropic with n=3,4.5 and anisotropic with n=3), we show that Derwael Ice Rise is close to steady state but is best explained using ice anisotropy and moderate thinning. Our preferred, albeit not unique, scenario suggests that the ice divide has existed for at least 5000 years and lowered at approximately 0.03 m a−1 over the last 3400 years. Independent of the specific thinning scenario, our modeling suggests that Derwael Ice Rise has exhibited a local flow regime at least since the Mid-Holocene.
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isbreer; stratigrafi

The significant inputs of trace elements and rare earth elements from melting glaciers in Antarctic coastal waters - Kim, Intae; Kim, Guebuem; Choy, Eun Jung (Polar Research, 2015)
To evaluate the impact of modern glacier melting on the chemical enrichment of Antarctic coastal waters, we measured trace elements, including dissolved iron (Fe) and rare earth elements (REEs), together with dissolved inorganic nitrogen, phosphorous, silicate and dissolved organic carbon (DOC) in ice, snow and coastal seawater of Marian Cove in the northernmost part of Antarctica (62°S). There was an increase in the concentrations of Fe and other trace elements (Al, Mn, Cr, Ni, Co, Pb and REEs) between the bay mouth and the glacier valleys. Good correlations between salinity and these chemical elements indicate that the trend was mainly due to the influence of glacier meltwater (GMW). When the effect of GMW was quantified based on plots of its presence (average 5.7%) in the surface water of the cove, the concentrations of trace elements in seawater increased 18-fold for Fe, eight- to 10-fold for Al and Mn and up to four-fold for Cr, Ni, Co, Pb and REEs by GMW. However, the contribution of GMW to inorganic nutrients and DOC was negligible. The significance of GMW-borne REE contribution in this cove was further evidenced by middle REE enrichment in cove water. Our results suggest that the currently increasing glacier melting in Antarctica has a significant influence on the level of trace elements, particularly Fe, in cove water, which in turn may have a significant impact on the biogeochemistry of coastal seawater in Antarctica. Keywords: Iron; trace elements; rare earth elements; glacier melting; Antarctica; Marian Cove.
Keywords: Antarktis; biogeokjemi; isbreer; kjemiske analyser; sjøvann; smelting

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

Polythermal glacier hydrology: a review - Irvine-Fynn, Tristram D L; Hodson, Andrew J; Moorman, Brian J; Vatne, Geir; Hubbard, Alun L (Reviews of Geophysics, 2011)
The manner by which meltwater drains through a glacier is critical to ice dynamics, runoff characteristics, and water quality. However, much of the contemporary knowledge relating to glacier hydrology has been based upon, and conditioned by, understanding gleaned from temperate valley glaciers. Globally, a significant proportion of glaciers and ice sheets exhibit nontemperate thermal regimes. The recent, growing concern over the future response of polar glaciers and ice sheets to forecasts of a warming climate and lengthening summer melt season necessitates recognition of the hydrological processes in these nontemperate ice masses. It is therefore timely to present an accessible review of the scientific progress in glacial hydrology where nontemperate conditions are dominant. This review provides an appraisal of the glaciological literature from nontemperate glaciers, examining supraglacial, englacial, and subglacial environments in sequence and their role in hydrological processes within glacierized catchments. In particular, the variability and complexity in glacier thermal regimes are discussed, illustrating how a unified model of drainage architecture is likely to remain elusive due to structural controls on the presence of water. Cold ice near glacier surfaces may reduce meltwater flux into the glacier interior, but observations suggest that the transient thermal layer of near surface ice holds a hydrological role as a depth-limited aquifer. Englacial flowpaths may arise from the deep incision of supraglacial streams or the propagation of hydrofractures, forms which are readily able to handle varied meltwater discharge or act as locations for water storage, and result in spatially discrete delivery of water to the subglacial environment. The influence of such drainage routes on seasonal meltwater release is explored, with reference to summer season upwellings and winter icing formation. Moreover, clear analogies emerge between nontemperate valley glacier and ice sheet hydrology, the discussion of which indicates how persistent reassessment of our conceptualization of glacier drainage systems is required. There is a clear emphasis that continued, integrated endeavors focused on process glaciology at nontemperate glaciers are a scientific imperative to augmenting the existing body of research centered on ice mass hydrology.
Keywords: Antarktis; geografi; glasiologi; global oppvarming; hydrologi; innlandsis; isbreer; isbrem; polarområdene

Spatial modelling of wetness for the Antarctic Dry Valleys - Stichbury, Glen; Brabyn, Lars; Green, T G Allan; Cary, Craig (Polar Research, 2011)
This paper describes a method used to model relative wetness for part of the Antarctic Dry Valleys using Geographic Information Systems (GIS) and remote sensing. The model produces a relative index of liquid water availability using variables that influence the volume and distribution of water. Remote sensing using Moderate Resolution Imaging Spectroradiometer (MODIS) images collected over four years is used to calculate an average index of snow cover and this is combined with other water sources such as glaciers and lakes. This water source model is then used to weight a hydrological flow accumulation model that uses slope derived from Light Detection and Ranging (LIDAR) elevation data. The resulting wetness index is validated using three-dimensional visualization and a comparison with a high-resolution Advanced Land Observing Satellite image that shows drainage channels. This research demonstrates that it is possible to produce a wetness model of Antarctica using data that are becoming widely available. Keywords: GIS; water; Antarctica; remote sensing.
Keywords: Antarktis; geografi; hydrologi; innsjø; isbreer; satellitt bilder; snø; vann; økosystemer